IMPLEMENTASI KEBIJAKAN PENCEGAHAN STUNTING DI KABUPATEN BANDUNG BARAT - Rafih Sri Wulandari (FISIP Universitas Langlangbuana, 2019)
Stunting is a chronic malnutrition problem caused by a lack of nutritional intake in a long time, resulting in growth disorders in children, namely the child's height is lower or shorter (dwarf) than his age standard. The government pays special attention to the community in relation to this stunting by making government policies and Policy Frameworks for dealing with Stunting through Law No.36 / 2009 on Health and Law No.18 / 2019 on Food. Both policies are supported by presidential regulation No.42 / 2013 concerning the acceleration of nutrition improvement. Related to stunting prevention covered by the 2015-2019 National Medium Term Development Plan (RPJMN), there is even a national strategy to accelerate the prevention of Stunting 2018-2014. However, after so many years the policy has not been implemented yet to solve the existing problems. In West Bandung Regency Based on data from Bappeda and Data from the Health Office there are ten (10) villages which are classified as Stunting emergencies. Based on this, it is necessary to increase the implementation of stunting management policies in West Bandung Regency through communication, outreach and education about the impact of stunting on children's growth and development which will affect their future, with the hope that the community can play an active role in prevention and can reduce the number of children affected by Stunting in the West Bandung Region.